Tecnologias na atenção primária à saúde: a atuação de enfermeiras na perspectiva do empoderamento social - Ordoñez, Lina Karina Bernal (2019)
This thesis has as a general objective to analyze the work process of nurses in Primary Health Care (PHC) in the development of technologies for the empowerment of users and health teams. It is a qualitative and exploratory research, in a case study modality, carried out with nurses from a small municipality in the state of São Paulo. To produce two empirical data, the following strategies were used: semi-structured interview, systematic observation and field diary recording. Was conducted 09 interviews, one with a nurse responsible for the coordination of the PHC of the municipality and 08 with nurses from family health units. Systematic observation of the work process of three nurses selected from the interviews was carried out. The information obtained from the observation was recorded in the field diary and completed the production of two research data. The given forums are analyzed in light of two principles of Social Empowerment anchored in liberating education and concepts related to the organization of the Process of Work in Health. To characterize the work process of PHC nurses, it was used as a tool for the construction of an analyzing flowchart. For general analysis, two data were used as reference for content analysis, in thematic modality. The results show a superficiality in the understanding of empowerment by nurses, instead of conceiving empowerment as giving voice to the PHC team and users. The flowcharts will allow a description of the activities carried out by nurses in PHC and will show the dynamics of the work process and differences in the productive process of each nurse: one in which live work is predominant and others in which dead work prevails. An analysis of the content of its origin in three categories: technologies with potential for the empowerment of users; technology with the potential for the empowerment of the health team and technology with the potential for the empowerment of nurses. The results showed the possibility of using various technologies with potential for social empowerment in PHC, even if their realization is conditioned by political and social determinants.